Ethics In Public Administration As The Foundation Of Good Governance In The Digital Era - Musri; Sayid Anshar; Puryanto; Onzukrisno; Baso Ifing (LPPM Universitas Ekasakti, 2025)
Administrative Ethics as the Foundation of Good Governance in the Digital Era discusses the importance of administrative ethics in establishing good governance, particularly within the ever-evolving digital context. In the digital era, new challenges have emerged in public service delivery, including the need for greater transparency, accountability, and responsiveness. This study aims to identify how administrative ethics can serve as a pillar in realizing the principles of good governance. Employing a qualitative approach, this research analyzes various policies and administrative practices implemented across different government agencies. The findings indicate that the application of administrative ethics not only improves the quality of public services but also strengthens public trust in the government. However, several challenges remain, such as the digital divide and the need for ethics training among civil servants. This study recommends the development of more inclusive policies and ongoing training to enhance ethical awareness within the bureaucracy.